United for Justice: Global Muslim Group`s Responses to the Israeli Occupation in Palestine - Aswar, Hasbi; Nuril Fajri, Ulya; Rizqi Mulia, Jalaluddin (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
The issue of Israeli occupation in Palestine has become a major concern of the Islamic world and the international community for more than seven decades. Various Islamic organizations respond to this issue through social action, humanity, diplomacy, and military resistance. This article analyzes various Islamic movements that support Palestine by using the concept of social movement from Tilly & Tarrow (2015), which includes a sustainable claim campaign, public action, solidarity show, and dependence on networks and organizations. This study uses a qualitative approach by collecting data from various online sources, including academic publications, organizational reports, and social media. The results showed that Muhammadiyah and Nahdlatul Ulama (NU) adopted a humanitarian and diplomatic approach to supporting Palestine by raising funds, taking solidarity actions, and advocating in international forums. The Salafi movement is more focused on the spread of religious da'wah and education; Ikhwanul Muslimin, linked to Hamas, led a direct military struggle against Israel. Meanwhile, Hizbut Tahrir views that the release of Palestine can only be achieved through the restoration of the Islamic Khilafah by organizing a global advocacy campaign and mass mobilization. This study concluded that although the strategies and approaches of these organizations were different, their main objectives remained the same, namely rejecting the Israeli occupation and fighting for Palestinian independence.